Návrh konkurenční strategie firmy - Tesař, Karel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce je zaměřena na vytvoření konkurenční strategie malé rodinné firmy. Analyzuje současný stav firmy zabývající se statickou a projekční činností. Zkoumá působení vnějšího prostředí na firmu a analyzuje vnitřní prostředí. Definuje strategické cíle firmy, obsahuje návrh budoucí konkurenční strategie firmy a její časovou implementaci.

This diploma thesis is focused on creation of competitive strategy of small family firm. It analyses current status of a company, which is specialized in complete design and stress analysis of constructions. The thesis investigates impact of external enviroment on the firm and it also analyses internal enviroment. The thesis defines strategic targets, contains proposal of competitive strategy of the company and time of its implementation.
Proposal of Competitive Strategy of Company
Keywords: strategie; konkurenční strategie; konkurenční výhoda; hodnotový řetězec; marketingový mix; strategy; competitive strategy; competitive adventage; value chain analysis; marketing mix